COVID-19 health information needs of older adults from ethnic minority groups in the UK: a qualitative study. Issue 6 (20th June 2022) - Paudyal, Priyamvada; Skinner, Emily; Majeed-Hajaj, Saliha; Hughes, Laura J; Magar, Naresh Khapangi; Keeling, Debbie Isobel; Armes, Jo; Kulasabanathan, Kavian; Ford, Elizabeth; Sharp, Rebecca; Cassell, Jackie A
Abstract : Objective: This study aimed to identify the COVID-19 health information needs of older adults from ethnic minority groups in the UK. Study design: A qualitative study using semistructured interviews. Setting and participants: Indian and Nepalese older adults (≥65 years), their families (≥18 years) and healthcare professionals (HCPs) (≥18 years) engaging with these communities. Participants were recruited between July and December 2020 from Kent, Surrey and Sussex through community organisations. Results: 24 participants took part in the study; 13 older adults, 7 family members and 4 HCPs. Thirteen participants were female, and the majority (n=17) spoke a language other than English at home. Older participants mostly lived in multigenerational households, and family and community were key for providing support and communicating about healthcare needs. Participants' knowledge of COVID-19 varied widely; some spoke confidently about the subject, while others had limited information. Language and illiteracy were key barriers to accessing health information. Participants highlighted the need for information in multiple formats and languages, and discussed the importance of culturally appropriate avenues, such as community centres and religious sites, for information dissemination. Conclusion: This study, undertaken during the COVID-19 pandemic, provides insight into how health information can be optimised for ethnic minority older adults in terms of content, format and cultural relevance. The study highlights that health information interventions should recognise the intersection between multigenerational living, family structure, and the health and well-being of older adults, and should promote intergenerational discussion.